Association of SARS-CoV-2 Test Status and Pregnancy Outcomes. Issue 3 (25th September 2021) - Ahlberg, M.; Neovius, M.; Saltvedt, S.; Söderling, J.; Pettersson, K.; Brandkvist, C.; Stephansson, O.
Abstract : ( JAMA . 2020;324:1782–1785) Case reports and case series make up most of the studies on coronavirus disease 2019 (COVID-19) and pregnancy outcomes. Lacking are studies with a comparison group. The aim of this study was to compare women in labor infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with those who were not infected.